Estimating the Costs of International Corporate Tax Avoidance: The Case of the Czech Republic - Petr Jansky (Charles University in Prague, Institute of Economic Studies (IES), 2016)
International corporate tax avoidance by multinational enterprises likely lowers the Czech Republic's corporate income tax revenue, but it is not clear by how much. To clarify this I first review existing estimates of the costs of international corporate tax avoidance to government revenue worldwide. I then discuss research and revenue estimates relevant for the Czech Republic and develop a few new ones, albeit only illustrative. None of the existing research focused on the Czech Republic nor the five recent international studies I examine provide reliable estimates for the Czech Republic. The extrapolations from these studies result into a range from 6 to 57 billion CZK (4-38 % of current corporate income tax revenue) with a median of 15 billion CZK (10 %) in annual corporate income tax revenue loss. This scale is comparable with the responses of 35 Czech experts with a median of 20 billion CZK (13 %). I conclude with a discussion of these rough estimates as well as questions for further research and policy recommendations.
Keywords: F23; H25; H26; O19; 330; corporate income tax; international taxation; tax avoidance; BEPS; Czech Republic